Prinsip Utama Gerakan Persatuan Kebangsaan Pelajar Islam Malaysia (PKPIM): (The Main Principles of National Union of Malaysian Muslim Students (PKPIM) Movement) - ZAHARI, MIOR MUHAMMAD SYAHIR (Online Journal of Research in Islamic Studies, 2024)
The fell of the Khilāfah Islāmiyyah system had caused the emergence of Islamic movements on some Muslim country such as al-Ikhwān al-Muslimūn from the Middle East and Jamā‘at al-Islāmi from India-Pakistan. Meanwhile in Malaysia, Angkatan Belia Islam Malaysia (ABIM) emerge as one of the Islamic movements. Before ABIM was founded, the predecessors of it was from an Islamic student movement which was founded earlier known as Persatuan Kebangsaan Pelajar Islam Malaysia (PKPIM). Nowadays, there are some activists’ movements trying to fight for Islam. Unfortunately, they were using false approach such as religious extremism and liberalism. These confusions were caused by the lack of clear and right principles in those movements. The purpose of this article is to state and elaborate the main principles held and practised by PKPIM. This research approach is qualitative. Content analysis and descriptive were used as research design. The data was collected through documentation and observation. The concept of wasaṭiyyah in Islam was used as the conceptual framework to analyse the collected data. It was found out that the main principles practised by PKPIM were in comply with the principles of wasaṭiyyah in Islam.